Interleukin-34 expression in ovarian cancer: a possible correlation with disease progression. (23rd December 2019) - Endo, Hiraku; Hama, Naoki; Baghdadi, Muhammad; Ishikawa, Kozo; Otsuka, Ryo; Wada, Haruka; Asano, Hiroshi; Endo, Daisuke; Konno, Yosuke; Kato, Tatsuya; Watari, Hidemichi; Tozawa, Akiko; et al.
Abstract: Ovarian cancer is the second-most lethal gynecological malignancy and the seventh-commonest cause of cancer-related death in women around the world. Most of the ovarian cancer patients are diagnosed at advanced stages and suffer from recurrence after primary cytoreductive surgery and standard first-line chemotherapy. Thus, the successful management of ovarian cancer patients requires the identification of factors that contribute to progression and relapse. Interleukin-34 (IL-34) is a novel cytokine that acts as a tissue-specific ligand of colony-stimulating factor-1 receptor (CSF-1R). In cancer, IL-34 exerts pro-tumorigenic functions that promote tumor growth, metastasis, angiogenesis, immune suppression and therapeutic resistance. In this study, we evaluate the impact of IL-34 on progression and survival of ovarian cancer patients. First, IL-34 was found to be expressed in several human ovarian cancer cell lines and cancer tissues from patients. The expression of IL-34 was enhanced by cytotoxic chemotherapy in ovarian cancer cell lines and cancer tissues from chemotherapy-treated ovarian cancer patients. Importantly, high IL-34 expression correlated with worse progression-free survival (PFS) and overall survival in different cohorts. The assessment of PFS based on a combination between IL34 expression and other related genes such as CSF1R and CD163 helped further to reach more statistical significance compared with IL34 alone. Furthermore, in the murine ovarian cancer cell HM-1 in vivo model, it was suggested that IL-34-derived tumor cells was correlated with tumor progression and survival by modulating the immune environment. Collectively, these findings indicate a possible correlation between IL-34 expression and disease progression in ovarian cancer patients and the mouse model. Abstract : Potential roles for IL-34 in ovarian cancer